2022
DOI: 10.1002/rmv.2375
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory viruses directly from clinical samples using next‐generation sequencing: A literature review of recent advances and potential for routine clinical use

Abstract: Acute respiratory infection is the third most frequent cause of mortality worldwide, causing over 4.25 million deaths annually. Although most diagnosed acute respiratory infections are thought to be of viral origin, the aetiology often remains unclear. The advent of next‐generation sequencing (NGS) has revolutionised the field of virus discovery and identification, particularly in the detection of unknown respiratory viruses. We systematically reviewed the application of NGS technologies for detecting respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…[ 3 ] However, alternative and complementary technologies are also necessary for this effort as there exist barriers to the accessibility of sequencing technologies (i.e., rising costs and sizeable necessary sequencing volumes). [ 4 , 5 ] Furthermore, leveraging the SARS-CoV-2 monitoring to include co-occurring pathogens in the community, including other respiratory viruses that cause similar symptoms, is critical to accurately determine community health and disease prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] However, alternative and complementary technologies are also necessary for this effort as there exist barriers to the accessibility of sequencing technologies (i.e., rising costs and sizeable necessary sequencing volumes). [ 4 , 5 ] Furthermore, leveraging the SARS-CoV-2 monitoring to include co-occurring pathogens in the community, including other respiratory viruses that cause similar symptoms, is critical to accurately determine community health and disease prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Furthermore, mNGS enables pathogen subtyping/genotyping, identification of drug resistance markers, and molecular-based epidemiological studies. 9,19,20 Although recent studies have demonstrated the power of mNGS in diagnosing respiratory infection in different parts of the world, 6,9,14,21 the current data from South Africa/Africa at large on the clinical diagnostic utility of mNGS in SARI are still limited, 22 especially in comparison to the performance of mRT-PCR in paediatric patients. Additionally, the increasing need for prompt analysis of generated mNGS data has birthed several user-friendly, nontechnical, yet sensitive web-based mNGS bioinformatic analysis tools.…”
Section: Introductionmentioning
confidence: 99%
“…Future solutions to the existing NGS platform difficulties may result from the quick advancement of NGS technologies and bioinformatics pipelines [37]. Therefore, in the near future, we may anticipate that NGS technique will be predominantly used in wet lab for routine work at a cheap cost and providing more effective therapy, and monitoring new viruses [39].…”
Section: Discussionmentioning
confidence: 99%